PSYCHOLOGICAL ANALYSIS OF AGGRESSIVE BEHIVIOR IN ADOLESCENCE - Abdullaeva Nigora Rahimovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article is about some kinds of aggressivety, appearing at teenagers during the period of their forming, and becoming of personality.